An oil risk management system based on high-resolution hazard and vulnerability calculations. (February 2017) - Azevedo, Alberto; Fortunato, André B.; Epifânio, Bruno; den Boer, Sérgio; Oliveira, Eduardo R.; Alves, Fátima L.; de Jesus, Gonçalo; Gomes, João L.; Oliveira, Anabela
Abstract: A new oil risk management system is proposed herein. Risk is computed in a quantitative way, combining a detailed hazard maps generated with a process-based oil spill model over an unstructured computational grid, and a spatially detailed methodology for vulnerability analysis. The system has a web interface that serves as a single point of access to both emergency-driven and risk-management products. The system's products are made available to decision makers and emergency response agents through a WebGIS portal. The paper describes the methodological bases and application of a risk-assessment tool that provides hazard, vulnerability and risk assessment maps for oil spills in coastal areas. The system is demonstrated in the Aveiro lagoon. The hazard maps are obtained from the analysis of an oil spill scenarios database, generated for the climatological conditions most prone to the occurrence of an oil spill event in the study region. Several vulnerability indexes are considered (namely physical, socio-economical, biological and global vulnerability indexes) and adapted to consider the intertidal areas, instead of the commonly-used coastline representation of the vulnerability indexes usually found in the literature. This new feature was possible due to the capability of the oil spill model to represent the process of oil retention and re-suspension in the intertidal zones. The methodology and the risk management system and its WebGIS interface are of generic nature and can be applied to other hazards in coastal zones. Highlights: High-resolution risk assessment methodology. Hazard and vulnerability maps for oil spill events in coastal environments. Unstructured high-resolution hydrodynamic and oil spill models. Oil spill coastal retention and re-suspension processes.